A New Era of Muscarinic Acetylcholine Receptor Modulators in Neurological Diseases, Cancer and Drug Abuse - Helena Tsimpili; Grigoris Zoidis (Pharmaceuticals)
The cholinergic pathways in the central nervous system (CNS) play a pivotal role in different cognitive functions of the brain, such as memory and learning. This review takes a dive into the pharmacological side of this important part of CNS function, taking into consideration muscarinic receptors and cholinesterase enzymes. Targeting a specific subtype of five primary muscarinic receptor subtypes (M1-M5) through agonism or antagonism may benefit patients; thus, there is a great pharmaceutical research interest. Inhibition of AChE and BChE, orthosteric or allosteric, or partial agonism of M1 mAChR are correlated with Alzheimer’s disease (AD) symptoms improvement. Agonism or antagonism on different muscarinic receptor subunits may lessen schizophrenia symptoms (especially positive allosteric modulation of M4 mAChR). Selective antagonism of M4 mAChR is a promising treatment for Parkinson’s disease and dystonia, and the adverse effects are limited compared to inhibition of all five mAChR. Additionally, selective M5 antagonism plays a role in drug independence behavior. M3 mAChR overexpression is associated with malignancies, and M3R antagonists seem to have a therapeutic potential in cancer, while M1R and M2R inhibition leads to reduction of neoangiogenesis. Depending on the type of cancer, agonism of mAChR may promote cancer cell proliferation (as M3R agonism does) or protection against further tumor development (M1R agonism). Thus, there is an intense need to discover new potent compounds with specific action on muscarinic receptor subtypes. Chemical structures, chemical modification of function groups aiming at action enhancement, reduction of adverse effects, and optimization of Drug Metabolism and Pharmacokinetics (DMPK) will be further discussed, as well as protein–ligand docking.